Comparative Clinical Efficacy of Oil Prepared with Stem Bark and Fruit of Shirisha in the Management of Darunaka (Dandruff) - A Randomised, Single Blind Clinical Study (International Journal of Ayurveda and Pharma Research, 2025)
Darunaka, a Kshudra Roga classified under Kapalagata Roga in Ayurveda, is a common scalp disorder characterized by Kandu (itching), Kesacyuti (falling of hair), Ruksata (dryness), Tvaksputana (scaling/cracking of skin). It primarily arises due to vitiation of Vata and Kapha Doshas. Despite being non-fatal, it significantly impacts an individual's quality of life and aesthetics. This study aimed to comparative clinical efficacy of oil prepared with stem bark and fruit of Shirisha in the management of Darunaka (dandruff), assessing its role in Dosha Samana (pacification), symptom relief, and overall patient wellness. A clinical study was conducted involving patients diagnosed with cardinal symptoms of Darunaka. The trial formulation was administered as external application for 30 days. Classical Ayurvedic diagnostic criteria, as well as modern clinical parameters, were employed for assessment. Pre- and post-treatment observations were documented, focusing on signs such as Kandu, Kesacyuti, Tvak ruksata, and Tvaksputana. The results indicated a significant reduction in classical signs and symptoms of Darunaka. Improvements were noted in scalp health, reduction in itching. The therapy was well-tolerated by all participants, with no adverse effects reported. The study reinforces the efficacy of classical Ayurvedic approaches and suggests further large-scale research to validate these findings and integrate traditional treatments into contemporary scalp care.